1988
DOI: 10.1007/bf01644307
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Yersinia enterocolitica in man

Abstract: Ten patients with chronic Yersinia enterocolitica infections are described. The initial diagnosis was made by culture, significant agglutinin titres and indirect immunofluorescence (IF) on biopsies. During the chronic phase, culture and agglutinin titres were negative, but specific serum IgA and IgG antibodies reactive with at least two, i.e. the 36 kDa and the 46 kDa, virulence-associated released proteins were demonstrated in nine patients by immunoblot techniques. One patient had only IgG antibodies. The ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0
4

Year Published

1990
1990
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(65 citation statements)
references
References 13 publications
1
57
0
4
Order By: Relevance
“…Despite the importance of T lymphocytes in protection against Yersinia spp., it has been shown that this response does not always protect the host infected with Y. pseudotuberculosis or Y. enterocolitica against persistent infections [57][58][59][60]. These findings and our study suggests that Yersinia may cripple DC function to durably inactivate these responses.…”
Section: Discussionmentioning
confidence: 45%
“…Despite the importance of T lymphocytes in protection against Yersinia spp., it has been shown that this response does not always protect the host infected with Y. pseudotuberculosis or Y. enterocolitica against persistent infections [57][58][59][60]. These findings and our study suggests that Yersinia may cripple DC function to durably inactivate these responses.…”
Section: Discussionmentioning
confidence: 45%
“…Comparing the agglutination reaction with determination of specific anti-IgA and anti-IgG to Yops in culture-positive patients, it was clear that the anti-Yops are far more sensitive and reliable for diagnosis of Yersinia-associated disease. This was previously shown.6,7> 14,15 We could not associate the systemic forms with predisposing factors such as malignancy, hematologic disorders and iron overload. 16 We were impressed by the severity of the lymphad enopathy, which resembled that of disorders such as malignant lymphoma.…”
Section: Discussionmentioning
confidence: 50%
“…Persis tence of infection and antigens may be responsible for or involved in these complications. 15 Antibiotic treatment does not influence the course and duration of uncomplicated enteritis,14,18 and cur rently we do not advise antibiotic treatment in children younger than 6 years of age with enteritis in our area.…”
Section: Discussionmentioning
confidence: 78%
“…Diagnosis is not easy because the disease has diverse clinical presentations and stool cultures require specific laboratory methods, most of which are not per formed routinely. Furthermore, stool cultures and serology by demonstration of circulating agglutinins are often nega tive in the more complicated forms (2,3), and both may contribute to underestimation of the disease, In 1982 we began a study on Yersinia infections. At first all patients with enteritis were cultured for Y. enterocolitica and their physicians were asked to record all symptoms in cases with positive culture.…”
Section: Introductionmentioning
confidence: 99%